PERAN KUNCI HRD DALAM MENGAKSELERASI KOMPETENSI SDM (SUMBER DAYA MANUSIA) MENUJU MEA (MASYARAKAT EKONOMI ASEAN) - triasningrum, frida widyawati; Nafiah, Zumrotun; Sukarsono, Sukarsono (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2025)
In the era of globalization, the Fourth Industrial Revolution, and regional economic integration such as the ASEAN Economic Community (AEC), the role of Human Resource Development (HRD) has become increasingly strategic in developing competitive and adaptive human capital. HRD serves not only as a training facilitator but also as a strategic partner responsible for managing employee competencies through data-driven and industry-relevant approaches. This study aims to evaluate the role of HRD in enhancing organizational competitiveness through holistic and internationally oriented recruitment, training, and human capital development strategies. A descriptive qualitative method with an exploratory approach was used to understand the dynamics of HR management in the context of AEC and digital transformation. The results show that leading companies have integrated digital technologies in recruitment and training processes, applied competency-based training, and emphasized foreign language proficiency and cross-cultural communication. Furthermore, the success of human resource development is also influenced by collaboration between government, industry, and educational institutions in creating an inclusive policy and training ecosystem. Therefore, HRD plays a crucial role in building organizational competitive advantage and preparing a workforce capable of adapting to global challenges.